Comparison between SCOFF and EAT-26: an Italian Study on Young Female Adults - Chinello, A.; Corlazzoli, G.; Scuotto, R.S.; Cadeo, S.; Zappa, L.E.; Ricciardelli, P. (Journal of Psychology and Psychotherapy Research, 2024)
Early screening for eating disorders often occurs in primary care or in non-psychiatric settings by using rapid and easy questionnaires, such as EAT-26 and the SCOFF. Here, the study compares the Italian translations of SCOFF and EAT-26 to confirm their screening validity and risk distribution in a non-clinical sample composed by young women (aged 18-30 years). Our findings show a strong risk correlation between the two tools, with frequent and overlapped questions exploring similar constructs. However, mismatching results regarding the detection of clinical risk for eating disorders involve about a quarter of the sample, mostly due to their internal specificity/sensitivity, translation discrepancies, tool training and use modality. In general, both screening tools are reliable for EDs detection in the general population. In the case of EAT-26, the combined use of both questionnaires improve robustly the risk detection (+23%) for eating disorders in young female adults, especially in universities and work places adopting an online administration. Further studies may occur to better understand the specific factors influencing mismatching results, in terms of EDs risk, between the two questionnaires.